Cytoreductive Surgery and Hyperthermic İntraperitoneal Chemoterapy for Advance Gastric Cancer Associated Peritoneal Carcinomatosis Single Centre Unit for 10 Consecutive Patients - Özgül Düzgün; Sema Yüksekdağ; Murat Kalın; Şenol Çomoğlu; Semra Yanık; Ömer Faruk Özkan; Neşet Köksal (Haseki Tıp Bülteni, 2019)

(untitled)
Aim:Hyperthermic intraperitoneal chemotherapy with cytoreductive surgery has a positive effect on survival in advanced abdominal cancers. We aimed to present our experience with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy in gastric cancer patients with peritoneal carcinomatosis and a review of the literature.Methods:Ten patients (seven male, three female) who were diagnosed with gastric cancer between June 2017 and November 2018 were included in the study. Data on demographic characteristics, short-term follow-up results, surgical findings, peritoneal carcinomatosis index score, completeness of cytoreduction score, and morbidity and mortality rates were retrospectively analyzed.Results:The mean age of the patients was 60.3 years. The mean follow-up period was six months (1-15 months). One patient developed an anastomotic leak. In the other nine cases, there was no morbidity leading to mortality.Conclusion:While gastric cancer with peritoneal carcinomatos has a poor survival, less than six months with non-operative approach, treatment with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy offers better outcomes and overall survival. Our first results in our study with a limited number of patients are satisfactory and multicentric randomized studies are needed on this subject.